Synthesis of RAFT‐Mediated Amphiphilic Graft Copolymeric Micelle Using Dextran and Poly (Oleic Acid) toward Oral Delivery of Nifedipine. Issue 20 (10th September 2018) - Karmakar, Puja Das; Seesala, Venkata Sundeep; Pal, Aniruddha; Dhara, Santanu; Chatterjee, Soumit; Pal, Sagar
ABSTRACT: A novel, pH‐responsive supramolecular graft copolymeric micelle, composed of dextran and poly (oleic acid), has been synthesized through reversible addition fragmentation chain transfer polymerization with controlled M n and narrow polydispersity. The structural properties of the copolymer have been studied using FTIR and 1 H NMR spectral analyses. Critical micelle concentration (CMC) has been determined fluorometrically and conductometrically. The copolymer shows pH responsive micellar stability, which has been confirmed using DLS study. Dextran‐g‐OA copolymer demonstrates spherical morphology at CMC, while rod‐like assembly has been evidenced beyond CMC that is probably because of the structural alteration of copolymeric chains at higher copolymer concentration. Dextran‐g‐OA is noncytotoxic toward MG‐63 cells. As the self‐assemble nature of copolymer micelle promotes the oral administration of hydrophobic drugs, nifedipine (NFD, a hydrophobic drug) has been used as model drug that has been encapsulated substantially into the core of the micelle. The copolymer releases the loaded NFD at a much slower rate in simulated gastric fluid (pH 1.2) and relatively faster in simulated intestinal fluid (pH 7.4) with a cumulative release of ~95% within 24 h, suggesting an ideal candidate as nifedipine carrier. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2354–2363 Abstract : A novel, pH‐responsive supramolecular graft copolymeric micelle comprising dextran and poly (oleic acid) has been successfully synthesized through RAFT polymerization. The copolymer is biocompatible, noncytotoxic, and excellent carrier of the antibiotic nifedipine.